Bentuk Interaksi Parasosial pada Penggemar K-Pop Melalui Media Sosial X - Desy Dwi Renita; Dian Alfia Purwandari; Nurul Istiqomah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Korean wave has become very popular, especially in the field of music often referred to as “Korean pop” or “K-pop”, which is a fusion of various popular music genres from South Korea. With the internet and social media being easily accessible, K-pop in Indonesia is growing very fast. This research looks at the phenomenon of fan behavior towards their idols on social media, which leads to parasocial interactions because the ease of social media makes fans feel close to their idols. In parasocial interaction, a person acts towards media figures as if they are where they are. Parasocial interaction has forms including task attraction, identification attraction, and romantic attraction. Therefore, the purpose of this study is to find out how the form of parasocial interactions carried out by K-pop fans on X social media. This research uses a descriptive methodology that uses interviews and observations to collect data. The results showed that all informants actively engage in parasocial interactions with their idol, NCT, through social media X. This shows that the type of parasocial interaction that K-pop fans do on social media X. This shows that the types of parasocial interactions that occur in NCT fans through social media X are task attraction, identification attraction, and romantic attraction.